Presidential influence in the legislative process the passage of the RH Bill in the Philippine House of Representatives - Zialcita, Jean Paul L. (2019)
Access online through this link: https://journals.upd.edu.ph/index.php/pssr/article/view/8405/7347
Keywords: Reproductive Health Bill; Philippines. Congress. House of Representatives; Legislation